Coexistence effect of hypertension and angiotensin II on the risk of coronary heart disease: a population-based prospective cohort study among Inner Mongolians in China. (3rd August 2019) - Zhou, Yiting; Zhang, Rui; Wang, Guangli; Wang, Aili; Zhong, Chongke; Zhang, Mingzhi; Li, Hongmei; Xu, Tan; Zhang, Yonghong
Abstract: Objective: To investigate the coexistence effect of hypertension and angiotensin II on the risk of coronary heart disease based on a prospective study in an Inner Mongolian population of China. Methods: The participants were categorized into four subgroups according to hypertension status and median of angiotensin II level. Incident coronary heart disease (CHD) was defined as study outcome. A Cox proportional hazard model was used to compute hazard ratios (HRs) and 95% confidence intervals (CIs) of CHD across the four subgroups after adjusting for important confounding factors. Results: During an average 9.2 years of follow-up, a total of 75 incident CHD cases were observed. The cumulative incidence rates of CHD among normotensives with angiotensin II ≤49 pg/mL, normotensives with angiotensin II >49 pg/mL, hypertensives with angiotensin II ≤49 pg/mL and hypertensives with angiotensin II >49 pg/mL were 1.76%, 1.50%, 4.71% and 5.62%, respectively (log-rank test, p < .001). Compared to the normotensives, the multivariable adjusted HRs (95% CI) of CHD with hypertensives and Ang II >49 pg/mL were 2.43 (1.41–4.17) and 1.30 (0.81–2.07), respectively. Furthermore, compared to normotensives with angiotensin II ≤49 pg/mL, the multivariate-adjusted HRs (95% CIs) of CHD for normotensives with angiotensin II >49 pg/mL, hypertensives with angiotensin II ≤49 pg/mL and hypertensives with angiotensin II >49 pg/mL were 1.33 (0.60–2.91), 2.35 (1.16–4.76) and 3.00 (1.52–5.92), respectively ( p for trend <.05). The hypertensives with angiotensin II >49 pg/mL were at the highest risk of CHD. Conclusions: Hypertension not angiotensin II was an independent risk factor for incident CHD, but the coexistence of both hypertension and high angiotensin II level further increased risk of incident CHD among the Inner Mongolians.